Pidginization And Linguistic Features Of Saudi Pidgin Arabic (Journal of Namibian Studies : History Politics Culture, 2023)
Due to the economic opportunities in the oil-rich Gulf States, many people, chiefly from Asia, have moved to the region with the intention of improving their lives. According to Elbanna and Fatima (2023), this foreign workforce constitutes two-thirds of the population in the Gulf States (p. 292). Consequently, these people have been instrumental in creating Gulf Pidgin Arabic (GPA), especially Saudi Pidgin Arabic (SPA). In the last decade, GPA has been discussed from a linguistic perspective, as in Hobrom (1996), Almoaily (2013), and Aljutaily (2018). This pidgin exhibits interesting properties and differs from its lexifier Gulf Arabic (GA) in significant ways. Although early studies have presented a set of proposed properties of GPA that reveals multiple mismatches with its superstrate language (GA), almost none of them have noted the cross-linguistic typological features of GPA as spoken in different Gulf States in a single body of research. The current study explores our own first-hand examples and compares them to several studies conducted in various Gulf countries. Many examples fit nicely into the category of simplicity, while others might be a product of transfer; however, we were able to trace some signs of complexity and multifunctionality.